The promising immune checkpoint LAG-3 in cancer immunotherapy: from basic research to clinical application - Huo, Jin-Ling; Wang, Ya-Tao; Fu, Wen-Jia; Lu, Nan; Liu, Zhang-Suo (Frontiers in Immunology, 2022)
LAG-3, a type of immune checkpoint receptor protein belonging to the immunoglobulin superfamily, is confirmed to be expressed on activated immune cells, mainly including activated T cells. LAG-3 can negatively regulate the function of T cells, exerting important effects on maintaining the homeostasis of the immune system under normal physiological conditions and promoting tumor cells immune escape in the tumor microenvironment. Given its important biological roles, LAG-3 has been regarded as a promising target for cancer immunotherapy. To date, many LAG-3 inhibitors have been reported, which can be divided into monoclonal antibody, double antibody, and small molecule drug, some of which have entered the clinical research stage. LAG-3 inhibitors can negatively regulate and suppress T cell proliferation and activation through combination with MHC II ligand. Besides, LAG-3 inhibitors can also affect T cell function via binding to Galectin-3 and LSECtin. In addition, LAG-3 inhibitors can prevent the FGL1-LAG-3 interaction, thereby enhancing the human body's antitumor immune effect. In this review, we will describe the function of LAG-3 and summarize the latest LAG-3 inhibitors in the clinic for cancer therapy.